An Empirical Investigation of the Objectives and Constraints of Electronic Data Processing Departments - Hallam, Stephen F. (Academy of Management Journal, 1975)
Managers of electronic data processing (EDP) departments were asked to identify the highest priority objectives and most severe constraints for their departments. Their replies show general agreement on priorities and constraints. Rank orders of objectives and constraints are presented.